ANALISIS KENDALA DAN SOLUSI YANG DITERAPKAN OLEH GURU DALAM PEMBELAJARAN FIQIH DI KELAS 2 MI ARROUDHOH PANCASILA SAKTI - Indriani, Fitri; Amir Mukminin (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2025)
This study aims to identify the challenges faced in fiqh learning for 2nd-grade students at Madrasah Ibtidaiyah (MI) Arroudhoh Pancasila Sakti and explore the solutions implemented by teachers to address these challenges. The research questions are: What are the main constraints in fiqh learning for 2nd-grade students, and how do teachers overcome these challenges? The research employed a qualitative approach, collecting data through direct observation, in-depth interviews with teachers and students, and document studies. The research sample included fiqh teachers and 2nd-grade students at MI Arroudhoh Pancasila Sakti. The findings reveal that the primary challenges in fiqh learning include varying student comprehension levels, limited learning media, and difficulties in introducing abstract fiqh concepts to young children. The solutions implemented by teachers include using varied teaching methods, utilizing visual and audiovisual media, and applying individual approaches in guiding students. This research provides significant contributions to developing effective and engaging fiqh teaching strategies for elementary school students and offers valuable insights for educators in addressing fiqh learning challenges at the madrasah ibtidaiyah level.